OCTIC B-SPLINE COLLOCATION SOLUTION WITH NON-UNIFORM LENGTH FOR EIGHTH ORDER LINEAR DIFFERENTIAL EQUATION - Reddy, Y.Rajashekhar (International Journal of Research -GRANTHAALAYAH, 2017)
Presentation of Numerical solution for eighth order linear boundary value problem using Octic B-spline collocation method with non-uniform length is the subject of this paper. In this approach recursive form of B-spline function is used as basis in collocation method. Numerical examples are considered to show the advantage of recursive of B-spline function particularly in non-fixing the length of subintervals.